วัฒนธรรมองคกรกับองคกรแหงการเรียนรูของคณะศึกษาศาสตร มหาวิทยาลัยศิลปากร - ภัทรไชยอนันท์ กัญญภัคญา; อินทร์รักษ์ ประเสริฐ (วารสารการบริหารการศึกษา มหาวิทยาลัยศิลปากร, 2017)
การวิจัยครั้งนี้มีวัตถุประสงคเพื่อทราบ 1) วัฒนธรรมองคกรของคณะศึกษาศาสตร มหาวิทยาลัยศิลปากร 2) องคกร แหงการเรียนรูของคณะศึกษาศาสตร มหาวิทยาลัยศิลปากรและ 3) ความสัมพันธระหวางวัฒนธรรมองคกรและองคกรแหงการเรียนรูของคณะศึกษาศาสตรมหาวิทยาลัยศิลปากร การวิจัยครั้งนี้เปนการวิจัยเชิงพรรณา (Descriptive Research) กลุมตัวอยางที่ใช ไดแก บุคลากรคณะศึกษาศาสตร มหาวิทยาลัยศิลปากร จำนวน 159 คน เครื่องมือที่ใชในการวิจัยเปนแบบสอบถามเกี่ยวกับการวัฒนธรรมองคกร ตามแนวคิดของ แพตเตอรสัน เพอรกี้ และพารเกอร (Patterson, Purkey and Parker) และความเปนองคกรแหงการเรียนรู ตามแนวคิดของมารควอดท (Marquardt) สถิติที่ใชในการวิเคราะหขอมูลไดแก คาความถี่ คารอยละ คามัชฌิมเลขคณิต สวนเบี่ยงเบนมาตรฐาน และการวิเคราะหคาสัมประสิทธิ์สหสัมพันธของ เพียรสัน ผลการวิจัย พบวา 1. วัฒนธรรมองคกรของคณะศึกษาศาสตร มหาวิทยาลัยศิลปากร ในภาพรวมอยูในระดับมาก 2. องคกรแหงการเรียนรูของคณะศึกษาศาสตร มหาวิทยาลัยศิลปากร ในภาพรวมอยูในระดับมาก 3. วัฒนธรรมองคกรกับองคกรแหงการเรียนรู ของคณะศึกษาศาสตร มหาวิทยาลัยศิลปากรมีความสัมพันธในทางบวกกันทุกดานอยางมีนัยสำคัญทางสถิติที่ระดับ .01 THE ORGANIZATION CULTURE AND LEARNING ORGANIZATION OF THE FACULTY OF EDUCATION, SILPAKORN UNIVERSITY The purposes of this study were to study : 1) the Organizational Culture of the Faculty of Education, Silpakorn University, 2) the learning Organization of the Faculty of Education, Silpakorn University, and 3) the relationship between the Organizational Culture and the learning organization of the Faculty of Education Silpakorn University. A sample of this study was the personnel of the Faculty of Education, Silpakorn University, with the total of 159 respondents. This research was a Research the instruments for collecting the data consisted of the questionaire concerniny the Organizational Culture based on the concept of Patterson, Purkey and Parker and the learning organization based on the concept of Marquardt. The statistics used to analyze the data were frequency, percentage, arithemetics mean, standard deviation, and Pearson’s Product-moment correlation coefficient. The findings of this research were as follows : 1. The Organizational Culture of the Faculty of Education, Silpakorn University in overall was at high level. 2. The learning Organization of the Faculty of Education, Silpakorn University in overall was at high level. 3. There was a significant relationship between the Organizational Culture and the learning organization of of the Faculty of Education Silpakorn University at .01 level.